2011
DOI: 10.3109/02652048.2010.544418
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of semi-permanent hair dyes liposome

Abstract: This study used phospholipids from fresh egg yolks to prepare liposome-encapsulated semi-permanent hair dyes in different pH buffer solutions and evaluated the functions and colour fastness to washing of the dyes. The extraction ratio of egg yolk phospholipids was 5%, and the purity was 91.8%. Empty liposome solutions were then prepared using high-speed homogenizer with particle size 219-848 nm. After being stored at 4 °C for 28 days, the average particle size of the liposome-encapsulated dye formulas increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This lipids are very essential for the skin and also they could bound the keratin of hair layer. 11,12 It was shown that preventing colors in liposomes, protect hair color from washing and styling because of solubility properties of lipids. Dyes in liposomes improves the hair moisture balance, softness, and strength, also.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This lipids are very essential for the skin and also they could bound the keratin of hair layer. 11,12 It was shown that preventing colors in liposomes, protect hair color from washing and styling because of solubility properties of lipids. Dyes in liposomes improves the hair moisture balance, softness, and strength, also.…”
Section: Introductionmentioning
confidence: 99%
“…Dyes in liposomes improves the hair moisture balance, softness, and strength, also. 12 Under the light of these knowledge, this study aimed to prepare pomegranate peel extract (PE) loaded liposome formulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomes or phospholipid vesicles are amphoteric compounds containing both polar and nonpolar groups 2,3 . Liposomes are the assembling structures formed by surface-active biological lipids that are arranged with hydrophilic polar head groups exposed to the aqueous phase and hydrophobic fatty acid chains adhered together in the bilayer 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, liposomes are used in environmentally conscious fabric processing procedures in the textile industry to encapsulate dye molecules, in order to reduce environmental pollution ; the related processing techniques have already exhibited promising results [5]. Such liposome-encapsulated dye formulations have demonstrated outstanding coloring effects on coloring protein fibers, such as wool and silk, as liposomes enabled the formulations to dissolve fast, which increased the effectiveness of the coloring processes and also improved the antistatic and antishrinkage effects of the fabrics [6,7,8].…”
mentioning
confidence: 99%